2002
DOI: 10.1161/01.cir.0000021120.90970.b9
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Modulates Myocardial Oxygen Consumption in the Failing Heart

Abstract: Background-Endogenous nitric oxide (NO) has been reported to inhibit oxygen consumption in the normal heart, so that nonselective inhibition of NO synthase (NOS) caused an increase of myocardial oxygen consumption (MV O 2 ). Although endothelial NOS responses are depressed in congestive heart failure (CHF), inducible NOS (iNOS) may be expressed in failing myocardium. Methods and Results-This study tested the hypothesis that NOS inhibition would increase MV O 2 in the failing heart. CHF was produced in dogs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 43 publications
2
57
1
1
Order By: Relevance
“…28,29 GTN caused transient increases in heart rate and dP/dt (attributed to sympathetic-adrenergic reflex activation associated with a fall in blood pressure). However, the coronary blood flow response to GTN preceded the fall in blood pressure and increase in heart rate by Ϸ10 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 GTN caused transient increases in heart rate and dP/dt (attributed to sympathetic-adrenergic reflex activation associated with a fall in blood pressure). However, the coronary blood flow response to GTN preceded the fall in blood pressure and increase in heart rate by Ϸ10 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…CHF was produced by rapid ventricular pacing (7,9). After completion of studies during normal conditions, the pacemaker was activated at 230 beats/min; pacing was continued at this rate or adjusted upward to a maximum of 250 beats/min based on weekly assessments of hemodynamics obtained 30 min after deactivating the pacemaker.…”
Section: Methodsmentioning
confidence: 99%
“…In the in vivo situation, alterations in substrate preference in the failing heart, with decreased free fatty acid uptake and increased glucose utilization, could contribute to decreased oxygen utilization (10). In several previous reports pacing-induced CHF was associated with decreased MV O 2 (7,32,40), although Shen et al (37) found an increase in MV O 2 after development of CHF. These differing results may be related to differences in the duration and severity of CHF, as well as the specific protocols used to produce heart failure.…”
Section: Endothelial Dysfunction and Vascular Omentioning
confidence: 98%
See 1 more Smart Citation
“…Potential mechanisms are NO competition with oxygen over cytochrome-C oxidase and impaired enzyme activity (NO-related detrimental protein structural alterations of adenine nucleotide translocase, NADH CoQ reductase, succinate CoQ reductase 12 ). N G -nitro-L-arginine 13 reversed impaired oxidative phosphorylation 14 in failing canine hearts. This favorable effect of L-NNA on myocardial metabolism was not observed in the ischemic models.…”
Section: The Potential Role Of Nitric Oxide In Cardiogenic Shockmentioning
confidence: 90%